Crosslinked natural hydrogels for drug delivery systems - Noori Tahneh, Akram; Dashtipour, Bahareh; Ghofrani, Alireza; Keramati Nejad, Somayeh (Journal of Composites and Compounds, 2022)
Hydrogels made from a variety of materials may be used as a novel technology in regenerative medicine in the biomedical field. Hydrogels may be made using both chemical and physical processes, depending on the source material. Size, elastic modulus, swelling, and degradation rate are only a few of the many physical parameters that may be used to define hydrogels in experiments. Hydrogels made from natural polymers have been the focus of our review. Due to their remarkable biocompatibility and nontoxicity, simple gelation, and functionalization, hydrogels derived from natural polymers have received extensive attention in recent decades. As a result, natural polymer hydrogels are considered excellent biomaterials that have great potential in the biomedical field. Because carriers play such a large role in determining how far and how fast drugs reach their intended recipients, the need for intelligent drug delivery systems (DDSs) is on the rise. An outstanding goal of this study is to examine the impact that various crosslinking process parameters have on the drug delivery mechanism.